Faktor-Faktor Kesiapan Kerja Siswa Setelah Pengalaman Praktik Kerja Industri Kelas XI Jurusan (TKK) Teknik Konstruksi Kayu dan (DPKK) Desain Produksi Kriya Kayu SMKN 58 Jakarta - Dian Kurniawan; Rosmawita Saleh (Jurnal Pensil : Pendidikan Teknik Sipil, 2013)
The Objectives of this study to find out about job readiness factors after the students practical experience working wood construction engineering industry and production design woodwork SMK 58 Jakarta. Where the research was conducted in 58 SMK Jakarta majoring in construction engineering and design wood wood craft production from May to June 2013.This research method using survey methods. The population in this study is the class XI students majoring in Construction Engineering and Production Design Wood Craft Wood as many as 59 students and a sample of 49 students is determined by the sampling technique using simple random sampling. The instrument used was a questionnaire to gather data readiness factors working students after work experience industry practices. Reliability of the results obtained from the calculation of the value of r for job readiness factors, namely the value of 0.97 for the questionnaire that has been distributed to students.From the research that has been done on students, student work readiness factor that answers to the questionnaire students work readiness indicator has a mean value of 3.49. On indicators of industry experience work practices questionnaire answers students have an average value of 3.43.It can be concluded that the students' work readiness indicator most dominant and has the highest average value is 3.49. This suggests that high job readiness of every student after the experience of industrial work practices. Need for improvement in preparing students for industrial work practices in order to maximize the students to follow the practice of industry, labor and the role of government in the distribution of work graduate students SMK 58 Jakarta in particular and SMK in general